Potential Clinical Usefulness of Endothelial Adhesion Molecules in Predicting Risk of Type 2 Diabetes - Cui, MD, PhD, Wei; Song, MD, ScD, Yiqing (North American Journal of Medicine and Science, 2009)
Early endothelial dysfunction is a common antecedent of the metabolic or insulin resistance syndrome and may thus play an etiologic role in the pathogenesis of type 2 diabetes mellitus and associated complications. Elevated circulating levels of some endothelial adhesion molecules including e-selectin, intercellular adhesion molecule-1 (icam-1), and vascular cell adhesion molecule-1 (vcam-1) may reflect structural microvascular changes related to the pathophysiological processes of impaired insulin action and secretion. Elevated levels of soluble cellular adhesion molecules have been related to insulin resistance and other metabolic syndrome components. Evidence from prospective studies indicates that endothelial biomarkers, particularly e-selectin, may independently predict risk of type 2 diabetes among nondiabetic individuals in multiple populations. Circulating levels of endothelial adhesion molecules appear to have clinically significant prognostic value beyond inflammatory marker-crp in predicting future risk of type 2 diabetes.